2019
DOI: 10.1002/ccd.28098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of left ventricular end‐diastolic pressure with extent of myocardial ischemia, myocardial salvage and long‐term outcome in patients with ST‐segment elevation myocardial infarction

Abstract: Objectives We aimed to assess the association of left ventricular end‐diastolic pressure (LVEDP) with myocardial salvage and long‐term mortality in ST‐segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). Background The association of LVEDP with myocardial salvage or long‐term mortality in patients with STEMI has not been investigated. Methods This study included 1,312 patients with STEMI undergoing primary PCI between 2002 and 2007. LVEDP was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Increased LVEDP is a common finding in STEMI patients undergoing primary PCI, mainly due to decreased LV compliance and to diastolic dysfunction 10 . Furthermore, LVEDP is also a major determinant of coronary perfusion pressure and flow, 11 and has been shown to be a major predictor of adverse in‐hospital and long‐term adverse outcomes 12 , 13 and to be correlated with the extent of myocardial ischemia, reduced myocardial salvage and greater infarct size in STEMI setting 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased LVEDP is a common finding in STEMI patients undergoing primary PCI, mainly due to decreased LV compliance and to diastolic dysfunction 10 . Furthermore, LVEDP is also a major determinant of coronary perfusion pressure and flow, 11 and has been shown to be a major predictor of adverse in‐hospital and long‐term adverse outcomes 12 , 13 and to be correlated with the extent of myocardial ischemia, reduced myocardial salvage and greater infarct size in STEMI setting 14 …”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, LVEDP is also a major determinant of coronary perfusion pressure and flow, 11 and has been shown to be a major predictor of adverse in-hospital and long-term adverse outcomes 12,13 and to be correlated with the extent of myocardial ischemia, reduced myocardial salvage and greater infarct size in STEMI setting. 14 Lastly, no major adverse events linked to Impella usage in the context of SCAD were described, even though, the potential risk of propagating the intramural hematoma in SCAD vessels (due to the necessity for anticoagulation) and a higher risk of peripheral dis-section (in patients with concomitant fibromuscular dysplasia or other connective tissue disorders) should be considered. 7,9 4 | CONCLUSIONS Although hypothesis generating, our case report explores the possibility of using off-loading systems in complex SCAD patients presenting with hemodynamic instability for whom revascularization is not an immediate option.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an LVEDP greater than 24 mmHg had a worse prognosis and a higher incidence of mortality. These studies suggested LVEDP as an independent predictor of re-hospitalization and prognosis after STEMI (13)(14)(15). Satiroglu et al (16) identified STEMI as the cause of decreased left ventricular compliance, increased LVEDP, and impaired left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of CCI, Ndrepepa and Kastrati advance our understanding of the prognostic importance of left heart filling pressures in STEMI . The authors analyzed 1,300 STEMI patients and observed that an elevated LVEDP correlates with 8‐year mortality.…”
mentioning
confidence: 99%
“…Collectively, these studies identify LVEDP as a major predictor of outcomes after STEMI.In this issue of CCI, Ndrepepa and Kastrati advance our understanding of the prognostic importance of left heart filling pressures in STEMI. 3 The authors analyzed 1,300 STEMI patients and observed that an elevated LVEDP correlates with 8-year mortality. They further report that among patients with an LVEDP >25, 7.1% presented with cardiogenic shock.…”
mentioning
confidence: 99%